EVALUATION OF THE ADHESIVE INTERFACE BETWEEN ENAMEL AND A SINGLE-COMPONENT ADHESIVE APPLIED IN SELF-ETCHING AND SELECTIVE-ETCHING PROCEDURES - Gianina Iovan; Simona Stoleriu; Galina Pancu; Claudiu Topoliceanu; Catalina Maria Ciobanu; Sorin Andrian (Romanian Society of Oral Rehabilitation, 2014)
Aim of the study The aim of this study was to analyze the adhesive joint with enamel for a single-component system which can be used in either self- or selective-etching procedures. Material and methods The study group included 10 extracted third molars. Class V cavities were prepared in both lingual and labial surface and restored using a composite resin (Filtek Z550, 3MESPE) and the adhesive Single Bond Universal (3M ESPE). For the facial cavities, the adhesive was applied using a total-etch procedure. In the lingual cavities no etching gel was applied. The prepared teeth were split in an axial linguo-facial direction. The sections were observed by scanning electron microscopy using a VEGA II LSH (TESCAN) microscope. Results The images have showed that an adhesive joint was formed between composite and enamel regardless of the chosen technique (with or without etching). The adhesive layer interposed between the enamel and the composite resin was thicker in most samples were the specimens were subjected to acid etching. Conclusions Phosphoric acid pre-treatment could be beneficial for bonding to enamel when using mild self-etching adhesive systems.